Expression of cold-inducible RNA-binding protein in mouse spinal cord injury model - Xinhui Zhang; Yi Zhao; Jing Guo; Jingkun Chen; Xue Gao; Wentao Pan; Hengli Li; Shutong Yao; Yueying Zhang (PLoS ONE, 2025)
Objective To investigate the changes of Cold-Inducible RNA-Binding Protein (CIRBP) expression in mouse spinal cord injury model. Methods Seventy-five female C57BL/6 mice were randomly divided into five groups, 15 mice per group. According to different degrees of spinal cord injury, they were divided into Mild spinal cord injury, Moderate spinal cord injury, Severe spinal cord injury, Spinal cord amputation group, and Sham surgery group, all constructed with spinal cord percussion. All groups were dissected 1, 3, 5, 14, and 21 days after modeling. HE staining was used to observe the pathological changes in the spinal cord, The Basso mouse scale (BMS) was used for motor function scoring, and immunofluorescence was used to detect the expression of NeuN, IBA-1, and CIRBP in spinal cord tissues. Results HE results showed that inflammation was more pronounced in moderate, severe, and amputation injuries compared to the Sham surgery group. Moderate injury group and Severe injury group inflammation increased consistently over time. The severe injury group had severe tissue structure destruction and increased astrocytes significantly. Combined with the mouse BMS motor function score, the mouse severe injury group model was more stable. Compared with the Sham surgery group, there was a significant decrease in NeuN over time (P < 0.01) and a significant increase in IBA-1 and CIRBP (P < 0.01) in the severe injury group. Moreover, IBA-1 has significant co-localization with CIRBP. Conclusion CIRBP expression is significantly elevated in a mouse spinal cord injury model, Which may be related to the proliferation of microglia during spinal cord injury.